The Hindu Cosmopolitanism of Sister Nivedita (Margaret Elizabeth Noble): An Irish Self in Imperial Currents - Barua, Ankur (Harvard theological review, 2020)
Sister Nivedita (Margaret Elizabeth Noble), a prominent disciple of the Hindu guru Swami Vivekananda, creatively reconfigured some traditional Vedantic vocabularies to present the “cosmo-national” individual as one who is not antithetical to but is deeply immersed in the densities of national locations. As we situate Nivedita’s “vernacular cosmopolitanism” in post-Saidian academic cultures, one of the most striking features of her reiteration of the theme that Indians should seek the universal in and through the particularities of their national histories, cultural norms, and religious systems is that it is grounded in an East-West binary, where specific values, sensibilities, and themes are attributed to each pole—primarily material to the Western and spiritual to the Eastern. The locations of her life and thought within this binary generate a complex combination of certain highly perceptive readings of Eastern styles of living; spiritual idealizations and ahistorical romanticizations of some traditional Hindu beliefs, traditions, and customs; global visions of internationalist exchanges across humanity; and pointed critiques of the operations of empire—while, occasionally, she can herself challenge the binary as an inexact classification.